Factors influencing an advanced nursing practice service for people with intellectual disabilities - Schulenkorf, Tessa; Ilskens, Karina; Nadolny, Stephan; Gröndahl, Annika; Grunwald, Marie; Palmdorf, Sarah; Borchardt, Nina; Grebe, Christian; Maaß, Annika; Latteck, Änne-Dörte (European Journal of Public Health)
Background: People with intellectual disabilities (PWID) have less access to preventive healthcare services and are therefore more likely to suffer from certain chronic diseases. Advanced Practice Nursing (APN) can be a suitable approach for this group. However, APN is not yet widespread in all European countries. This intervention focuses on PWID in Hamburg, Germany, who receive case management and prevention focusing on stress, nutrition, mobility and addiction through community-based APN to improve their health status. We aimed to explore the facilitators, barriers and experiences of stakeholders in the context of the APN intervention. Methods: We conducted 90 semi-structured problem-centered interviews with PWID, family members, professional caregivers and prevention service providers in 2023 and 2024. We employed convenience sampling. Data were analyzed by qualitative content analysis with mixed inductive-deductive coding using MAXQDA. Results: Overall interviewees were satisfied with the intervention. It was reported that the clients exercised more, ate healthier, learned techniques to reduce stress and coped better with addiction. In addition, barriers to preventive services were reduced. We identified factors that positively influenced the success of the intervention: good interprofessional collaboration, successful relationship building with clients, concise goal setting and target group-specific work materials. Barriers were: neglect of the professional care network, difussion of agreements, lack of available prevention services, and communication problems. The results are preliminary. Conclusions: This is one of the first evaluation studies of an APN intervention for PWID in Germany. The results show that this new form of care can be implemented if the relevant stakeholders work together and good relationships with the clients are established. Specific goals should be defined and the professional carergivers should develop a community network. Key messages: APN is a suitable approach for disease prevention and health promotion for people with intellectual disabilities, given interprofessional collaboration and a well-established relationship with clients. Preventive healthcare for the target group is difficult to implement if the stakeholders do not work together and if there are insufficient suitable preventive services available in the community.